Stanowisko rządu Johna F. Kennedy’ego wobec kryzysu kongijskiego na forum ONZ (1961-1963) - Porczyńska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2007)
The Congo Crisis was one of the conflicts which involved economical and military power of the United Nations under presidency of John F. Kennedy. The United Stales had already aided Belgium but they weren’t able to solve that problem by using the US Army in Secessionist Katanga because it would lead to the direct confrontation with the USSR and its satellite countries. The second reason was connected with involvement of American private business in Katangian industry and the attempts of its exclusion made by Belgians or Patrice Lumumba’s forces. The John F. Kennedy Government attitude was determined by his predecessors policy of the containment, which should be successful in the decolonized areas. The John F. Kennedy Government attitude towards the United Nations during the Congo Crisis was determined by the majority in General Assembly created by newly independent African countries which supported the Soviet Union and his allies. That was the main cause why previously adopted “majority voting” in General Assembly was impossible for the John F. Kennedy Government.